2021
DOI: 10.2478/abm-2021-0020
|View full text |Cite
|
Sign up to set email alerts
|

Potential of amentoflavone with antiviral properties in COVID-19 treatment

Abstract: Amentoflavone is one of the flavonoids that are known for their antiviral effects and many of them are predicted to have inhibitory effects against severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome Coronavirus (MERS-CoV) enzymes 3-chymotrypsin-like protease (3CLpro) and papain-like protease (PLpro). Amentoflavone is a biflavonoid found in the herbal extracts of St. John's wort (Hypericum perforatum), Gingko biloba, Selaginella tamariscina, Torreya nucifera, and many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Hypericin was examined by Shih et al and showed inhibitory effect against hepatitis C virus replication via down-regulation of heme oxygenase-1 expression and deacetylation, and no cytotoxicity happens (Shih et al, 2018). According to research done by Singh et al, amentoflavone, an active flavonoid in H. perforatum L., has been shown to have antiviral properties, and many strains of H. perforatum L are anticipated to have inhibitory effects against SARS-CoV and MERS-CoV proteases such as papain (Pl pro ) and 3-chymotrypsin-like protease (3CL pro ) (Singh, 2021). In another study performed by Yalçın et al, it has been shown that H. perforatum L. can be an effective drug in the COVID-19 pandemic.…”
Section: Antiviral Assessmentmentioning
confidence: 99%
“…Hypericin was examined by Shih et al and showed inhibitory effect against hepatitis C virus replication via down-regulation of heme oxygenase-1 expression and deacetylation, and no cytotoxicity happens (Shih et al, 2018). According to research done by Singh et al, amentoflavone, an active flavonoid in H. perforatum L., has been shown to have antiviral properties, and many strains of H. perforatum L are anticipated to have inhibitory effects against SARS-CoV and MERS-CoV proteases such as papain (Pl pro ) and 3-chymotrypsin-like protease (3CL pro ) (Singh, 2021). In another study performed by Yalçın et al, it has been shown that H. perforatum L. can be an effective drug in the COVID-19 pandemic.…”
Section: Antiviral Assessmentmentioning
confidence: 99%
“…Amentoflavone is a bio-flavonoid found in herbs such as St. John’s wort, Gingko biloba , Selaginella tamariscina and Torreya nucifera , and acts as a potent inhibitor of CYP2C9 [ 27 ]. Molecular docking studies have shown that amentoflavone binds strongly to active site of the main protease (M pro ) of the COVID-19 virus.…”
Section: Herbs With Anti-covid-19 Properties: Cyp2c9 Inhibitors Inducersmentioning
confidence: 99%
“…However, administration of amentoflavone should be adjusted with other CYP2C9 inhibitors, e.g. warfarin, to avoid the risk of toxicity due to increased bioavailability during concurrent use [ 27 ]. A combination of traditional Chinese medicine (TCM) with clinically used drugs was considered as an effective approach to fight COVID-19 infection.…”
Section: Herbs With Anti-covid-19 Properties: Cyp2c9 Inhibitors Inducersmentioning
confidence: 99%
“…[ 37 , 67 , 81 ]. In recent years, during the coronavirus pandemic, amentoflavone has become a molecule of interest due to its antiviral effects against SARS-CoV-2 based on in vitro and in silico studies [ 82 , 83 ]. Amentoflavone in vitro has the potential to inhibit herpes simplex virus 1 (HSV-1) including Acyclovir (ACV) (antiviral drug) -resistant strains [ 84 ].…”
Section: Biological Activity Of Ginkgobiflavonoidsmentioning
confidence: 99%